PENGARUH KINERJA LINGKUNGAN DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN - Muhammad Luthfi Ramadhana; Indira Januarti (Diponegoro Journal of Accounting, 2022)
This study aims to analyze and to provide empirical proof of the effect of environmental performance on firm value, to analyze and to provide empirical proof of the effect of environmental performance on financial performance, to analyze and to provide empirical proof of the effect of financial performance on firm value, and to analyze and to provide empirical proof that financial performance can mediate the effect of environtmental performance on firm value.The population in this study are companies listed in the Program Penilaian Peringkat Kinerja Perusahaan (PROPER) and the Indonesia Stock Exchange (IDX) in 2017 to 2019. The total sample used in this study is 179 companies based on predetermined criteria. Environtmental performance is measured using the PROPER scoring, financial performance is measured using ROE, and firm value is measured using TOBIN’S Q equation. Data analysis was carried out by descriptive statistical analysis, classical assumption test, hypothesis testing, and Sobel test. The results of the analysis of this study indicate that the company's environmental performance does not have a positive effect on firm value, the company's environmental performance has a positive effect on the company's financial performance, the company's financial performance does not have a positive effect on firm value, and financial performance can mediate the effect of the environmental performance variable on the firm value variable.